Pengaruh Good Corporate Governance terhadap Kinerja Karyawan PT. Pupuk Kujang Cikampek: The Influence of Good Corporate Governance on Employee Performance at PT. Cikampek Kujang Fertilizer - Syah, Didin Nahrudin; Hasbullah, Rachmat; Solehudin, Solehudin (Universitas Muhammadiyah Sidoarjo, 2018)
Factors forming Good Corporate Governance, namely Transparency, Accountability, Responsibility, Independence and Fairness, support the performance of Employees of PT.Pupuk Kujang Cikampek and whether there are simultaneous factors that form Good Corporate Governance that are positively open to Employee Performance at PT. Pupuk Kujang Cikampek. This research was conducted using quantitative descriptive and verification methods, namely collecting, presenting, analyzing, and testing hypotheses, and making conclusions and suggestions. Samples were taken using the Simple Random Sampling method with a sample of 100 respondents from 135 employees. The results of this study can be concluded that Is a Factor Forming Good Corporate Governance on employee performance.